MICROWAVE RADIATION: APPLICATIONS IN FOODS AND MICROBIOLOGICAL IMPACTS ON MEAT - Menezes, Maria Fernanda; Simeoni, Caroline Posser; Poletto, Gabriela; Barin, Juliano; Cichoski, Alexandre; Menezes, Cristiano (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The demand for food, especially the consumption of meat and meat products, is increasing in countries that are in full development, however consumers are increasingly demanding about the quality of these foods. To meet this demand, many alternatives preservation have been proposed and investigated in order to reduce vegetative micro-organisms commonly associated with foodborne illness. Meat is an excellent substrate for microbial growth, behaves like authentic culture medium due to its intrinsic and environmental factors that allow the development of numerous microorganisms. The nonionizing radiation of microwaves is presented as a new possibility for microbial control of meat and meat products. This radiation is the transfer of heat through electromagnetic waves in the range 300-300.000 megahertz (MHz), promoted by waves of electrical and magnetic energy moving together through space. Microwaves have different applications in area of food technology, such as thawing, drying, extraction, pasteurization, decontamination and disinfection of utensils, however, the benefits and limitations of this technology in an industrial application must be analyzed and discussed. This study aims to review, investigate and discuss the general and specific applications of microwave radiation as an alternative or complementary method to traditional process of preservation of meat.